Vietnam: Public–Private Higher Education Debates in a Communist State - Chau, Quang (International Higher Education, 2022)
With private higher education emerging in the late 1980s and challenging the public monopoly that had long been the norm in Vietnam, debates arise. Apart from debates common in other countries, such as those related to access, quality, equity, and profit, public–private debates in the Vietnamese case also occur along the line of political correctness, and indirectly reveal policy makers’ limited understanding of, and inexperience with the private sector.